Electro-magnetohydrodynamic two fluid flow of ionized-gases with hall and rotation effects - Linga Raju, Temburu (Zielona Góra: Uniwersytet Zielonogórski)
An electro-magnetohydrodynamic (EMHD) two fluid flow and heat transfer of ionized gases through a horizontal channel surrounded by non-conducting plates in a rotating framework with Hall currents is investigated.
Keywords: magnetic and electric fields; immiscible flow; plasma; Hall effect; rotating frame; heat transfer; insulating plates